Regulation of plasma volume in male lowlanders during 4 days of exposure to hypobaric hypoxia equivalent to 3500 m altitude. (16th November 2020) - Schlittler, Maja; Gatterer, Hannes; Turner, Rachel; Regli, Ivo B.; Woyke, Simon; Strapazzon, Giacomo; Rasmussen, Peter; Kob, Michael; Mueller, Thomas; Goetze, Jens P.; Maillard, Marc; van Hall, Gerrit; et al.
Abstract : Key points: Acclimatization to hypoxia leads to a reduction in plasma volume (PV) that restores arterial O2 content. Findings from studies investigating the mechanisms underlying this PV contraction have been controversial, possibly as experimental conditions were inadequately controlled. We examined the mechanisms underlying the PV contraction evoked by 4 days of exposure to hypobaric hypoxia (HH) in 11 healthy lowlanders, while strictly controlling water intake, diet, temperature and physical activity. Exposure to HH‐induced an ∼10% PV contraction that was accompanied by a reduction in total circulating protein mass, whereas diuretic fluid loss and total body water remained unchanged. Our data support an oncotically driven fluid redistribution from the intra‐ to the extravascular space, rather than fluid loss, as the mechanism underlying HH‐induced PV contraction. Abstract: Extended hypoxic exposure reduces plasma volume (PV). The mechanisms underlying this effect are controversial, possibly as previous studies have been confounded by inconsistent experimental conditions. Here, we investigated the effect of hypobaric hypoxia (HH) on PV in a cross‐over study that strictly controlled for diet, water intake, physical activity and temperature. Eleven males completed two 4‐day sojourns in a hypobaric chamber, one in normoxia (NX) and one in HH equivalent to 3500 m altitude. PV, urine output, volume‐regulating hormones and plasma protein concentration were determined daily. Total body water (TBW) was determined at the end of both sojourns by deuterium dilution. Although PV was 8.1 ± 5.8% lower in HH than in NX after 24 h and remained ∼10% lower thereafter (all P  < 0.002), no differences were detected in TBW ( P  = 0.17) or in 24 h urine volumes (all P  > 0.23). Plasma renin activity and circulating aldosterone were suppressed in HH during the first half of the sojourn (all P  < 0.05) but thereafter similar to NX, whereas no differences were detected for copeptin between sojourns (all P  > 0.05). Markers for atrial natriuretic peptide were higher in HH than NX after 30 min ( P  = 0.001) but lower during the last 2 days ( P  < 0.001). While plasma protein concentration was similar between sojourns, total circulating protein mass (TCP) was reduced in HH at the same time points as PV (all P  < 0.03). Despite transient hormonal changes favouring increased diuresis, HH did not enhance urine output. Instead, the maintained TBW and reduced TCP support an oncotically driven fluid redistribution into the extravascular compartment as the mechanism underlying PV contraction. Key points: Acclimatization to hypoxia leads to a reduction in plasma volume (PV) that restores arterial O2 content. Findings from studies investigating the mechanisms underlying this PV contraction have been controversial, possibly as experimental conditions were inadequately controlled. We examined the mechanisms underlying the PV contraction evoked by 4 days of exposure to hypobaric hypoxia (HH) in 11 healthy lowlanders, while strictly controlling water intake, diet, temperature and physical activity. Exposure to HH‐induced an ∼10% PV contraction that was accompanied by a reduction in total circulating protein mass, whereas diuretic fluid loss and total body water remained unchanged. Our data support an oncotically driven fluid redistribution from the intra‐ to the extravascular space, rather than fluid loss, as the mechanism underlying HH‐induced PV contraction.